2018
DOI: 10.1021/acsearthspacechem.7b00123
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Phase Photo-oxidation of Brown Carbon Nitrophenols: Reaction Kinetics, Mechanism, and Evolution of Light Absorption

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the author manuscript from TSpace because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page. ABSTRACT 7Light absorbing organic aerosol particles, referred to as brown carbon, are geographically 8 widespread and can have an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
131
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 64 publications
11
131
0
Order By: Relevance
“…First, different matrices could quench the electronic excitation in the chromophores to a different extent. Another possibility is that photodegradation of BrC chromophores could be not due to direct photolysis but rather occurring through condensed-phase photosensitized reactions (Malecha and Nizkorodov, 2017;Monge et al, 2012), in which case the rate of decomposition would depend on concentration of photosensitizers in the samples as well as viscosity of the material (Hinks et al, 2016;Kaur et al, 2019). Lastly, other absorbing species, such as black carbon, could be shielding BrC chromophores from irradiation, altering the amount of radiation absorbed by BrC chromophores.…”
Section: Aging By Condensed-phase Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…First, different matrices could quench the electronic excitation in the chromophores to a different extent. Another possibility is that photodegradation of BrC chromophores could be not due to direct photolysis but rather occurring through condensed-phase photosensitized reactions (Malecha and Nizkorodov, 2017;Monge et al, 2012), in which case the rate of decomposition would depend on concentration of photosensitizers in the samples as well as viscosity of the material (Hinks et al, 2016;Kaur et al, 2019). Lastly, other absorbing species, such as black carbon, could be shielding BrC chromophores from irradiation, altering the amount of radiation absorbed by BrC chromophores.…”
Section: Aging By Condensed-phase Photochemistrymentioning
confidence: 99%
“…Several studies have characterized changes in the UV-Vis spectra of nitrophenols, common in BBOA, as they are exposed to UV radiation. For example, Hinks et al (2016) irradiated 2,4dinitrophenol incorporated in limonene secondary organic aerosol material and observed the absorbance decrease in the range of 250-320 nm, while the absorbance from 400 to 450 nm increased. Similarly, Zhao et al (2015) observed a photo-enhancement at 420 nm for a 4-nitrocatechol aqueous solution, in response to direct photolysis.…”
Section: Introductionmentioning
confidence: 99%
“…OC can be separated into two categories based on the formation nature. Primary organic carbon (POC) can be emitted from traffic emission (Huang et al, 2014), biomass burning (Simoneit, 2002), trash burning and cooking (Mohr et al, 2009). Secondary organic carbon (SOC) can be formed through the oxidation of volatile organic compounds (VOCs) or semivolatile POC (Hallquist et al, 2009).…”
Section: Secondary Organic Carbon (Soc) Estimation By the Mrs Methodsmentioning
confidence: 99%
“…Vione, et al [54] showed that OH radicals reacted faster than NO 3 radicals with 2-NP and 4-NP in aqueous solutions to lower the atmospheric levels of 2-NP below those of 4-NP. Hems and Abbatt [55] studied the aqueous-phase photo-oxidation of 2,4-DNP by OH radicals, identified numerous intermediate products thereof and showed the corresponding evolution of UV absorbance of the reacting solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many laboratories studied the aqueous-phase reactions of other substituted phenols of atmospheric interest like guaiacol, nitro-guaiacol, vanillin, or syringol [55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%